Altitude training and the use of hypoxicator. The debate
The New Zealand Coach is training a new concept. We asked a variety of people in the different sporting fields to comment on a topic, where comments received would be published in this issue. The topic put to the people was the debate over the use of an hypoxicator, which is claimed to allow altitude training at sea level to occur. A prime benefit of such a device could see enormous savings in overseas travel and expenses when preparing for an event. As a relatively new concept being introduced to sport, there have been limited studies into intermittent hypoxic training and therefore we still know little about its potential ergogenic effects and/or side effects. Debate has ensued in regard to the use of hypoxicators and their claimed benefits. The following questions were given as a guideline for comments: As a coach, what are your thoughts on the use of simulated altitude for enhancing performance at sea level, be it in a tent or hypoxicator? At what point does it become a moral dilemma or unethical to proceed in your mind. For example one could argue EPO as a replacement for altitude training? Is it a case of `if it`s not on the banned substances/methods list then it is okay`?